Analisis tingkat motivasi belajar PPKN dalam pembelajaran daring materi hubungan simbol dengan makna sila Pancasila pada peserta didik kelas IV Sekolah Dasar - Dhita Murdaya; Hasan Mahfud; Dwi Yuniasih Saputri (Universitas Sebelas Maret, 2021)
The purpose of this study is to analyze the level of motivation to learn Civics in online learning material relationship symbols with meaning sila Pancasila on the fourth grade students of SD Negeri Tegalrejo No.98 Surakarta. The method in this research is descriptive qualitative. Data collection in this study using a questionnaire, interview of teachers and learners, as well as the observation of teachers and learners. Data analysis in this research using data analysis Miles, Huberman and Saldaña. Data analysis includes data collection, data reduction, data presentation, and conclusion. The results of this study prove that the learning motivation of students of class IV SD Negeri Tegalrejo No.98 Surakarta, categorized into three categories. Category learning motivation high by 16.7%, medium category of 77,8%, and the low category of 5.5%. Motivational aspects of learning that are considered to determine the level of motivation of students learning is an aspect of the ARCS-V (Attention, Relevance, Confidence, Satisfaction, and Volition). The conclusion of this research, it was found that the level of learning motivation of students of class IV SD Negeri Tegalrejo No.98 is moderate. This is because the level of motivation to learn is also affected by the challenges in learning.